1993
DOI: 10.1161/01.cir.88.6.2517
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of adding low molecular weight heparin to the conventional treatment of stable angina pectoris. A double-blind, randomized, placebo-controlled trial.

Abstract: Patients with stable angina pectoris may be treated with Parnaparin in addition to aspirin and conventional antianginal medication. Side effects are negligible, and compliance is excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…It also increased the template bleeding time consistent with several reports on the antihemostatic effects of LMWH. [29][30][31][32][33][34] The bleeding time test, which remains the most reliable global marker of treatment-induced hemostasis impairment, [22][23][24][35][36][37] was therefore used for the safety assessment of PCA treatment infusion in the equiefficacious dose range. While the absence of significant increase in the bleeding time during PCA infusion does not exclude the possibility of bleeding side effects, 38 the direct comparison between LMWH and PCA strongly suggested that the latter was considerably safer.…”
Section: Discussionmentioning
confidence: 99%
“…It also increased the template bleeding time consistent with several reports on the antihemostatic effects of LMWH. [29][30][31][32][33][34] The bleeding time test, which remains the most reliable global marker of treatment-induced hemostasis impairment, [22][23][24][35][36][37] was therefore used for the safety assessment of PCA treatment infusion in the equiefficacious dose range. While the absence of significant increase in the bleeding time during PCA infusion does not exclude the possibility of bleeding side effects, 38 the direct comparison between LMWH and PCA strongly suggested that the latter was considerably safer.…”
Section: Discussionmentioning
confidence: 99%
“…A lower plasma fibrinogen level can be achieved by reducing cigarette smoking [37], by exercise [38,39] and in diabetic patients probably by improved metabolic control [19,20]. Fibrinogen lowering can also be achieved by heparin [40] or low molecular weight heparin [41] administration. In diabetic patients these results were confirmed for both heparin formulations and moreover for the glucosaminoglycan sulodexide [42].…”
Section: Conclusion: Is It Time For Intervention Trials?mentioning
confidence: 99%
“…This is the first study to demonstrate such an improvement. De creased fibrin formation has been shown by the same group [18] in patients with acute myocardial infarction treated with a high dose of LMWH (parnaparin 12,800 IU anti-Xa once a day) compared to a low dose of par naparin (6,400 IU once a day) or UFH (15,000 IU). Significantly lower levels of fibrinopeptide A (FpA) during the first 8 h after drug administration were observed in the high-dose parnaparin group, compared to the other two groups.…”
Section: Stable Angina and Myocardial Infarctionmentioning
confidence: 82%